Chloride-free hydrolytic sol–gel synthesis of Nb–P–Si oxides: an approach to solid acid materials. Issue 20 (7th October 2020) - Clayden, Nigel J.; Imparato, Claudio; Avolio, Roberto; Ferraro, Giarita; Errico, Maria E.; Vergara, Alessandro; Busca, Guido; Gervasini, Antonella; Aronne, Antonio; Silvestri, Brigida
Abstract : A straightforward and sustainable synthesis of Nb–P–Si acid solid materials was developed through a hydrolytic one-step sol–gel route avoiding organic solvents, foreign catalysts or additives starting from cheap and available precursors. Abstract : Solid acids are the green alternative for heterogeneous acid catalysis, in particular for industrial processes exploiting biomass. Niobium–phosphorus oxides are valid candidates owing to their specific acidic properties and tolerance to water, on the other hand their synthesis often involves hazardous precursors and complex multistep procedures. We have recently employed Nb2 Cl10 and POCl3 to synthesize Nb–P–Si mixed oxides with SiO2 content equal to 95 and 92.5 mol% and Nb/P molar ratios equal to 1 and 2, which showed remarkable catalytic activity and water stability in different biorefinery reactions. Here we propose a more sustainable hydrolytic sol–gel route to obtain these materials, starting from ammonium niobium oxalate hydrate and phosphoric acid. The one-pot procedure occurs in water at room temperature, with safe, available and inexpensive precursors, and does not require any catalyst, additive or organic solvent resulting in an energy-efficient protocol. The structural characterisation of the gel-derived solids, performed by FTIR, Raman and 29 Si– 31 P solid state NMR spectroscopies, demonstrates that the designed procedure affords homogeneous samples at the microscopic level with good reproducibility, thus it represents a viable green route for the development of efficient biomass conversion catalytic cycles. Preliminary acid site characterisation and flow reactor experiments in gas-phase ethanol conversion to ethylene demonstrate that these catalytic materials are strongly acidic.